Profiling Shopping Mall Costumer Based on Demographics and Shopping Motivation - Rahmawati Rahmawati (Asosiasi Peneliti Manajemen Adat Indonesia, 2019)
Nowadays malls play a major role in consumer’s lifestyle. This research aims to (1) Identify the segments from shopping mall customer (2) Describe the profiles of shopping mall segments formed (3) Explain the differences each characteristics between segments are formed. This research is using confirmatory factor analysis and cluster analysis. This study revealed six factor shopping motivation such that gratification seeking, social shopping, value shopping, brand loyalty, utilitarian, and hedonic shopping. The result suggests that there istwo shopper segment, hedonic shopper and utilitarian shopper. Each segment was profiled in terms of shopping motivation and demographics.